Dakwah Tauhid Muhammad Nafis al-Banjari (1150 H/1735 M) - Maimunah Zarkasyi (TSAQAFAH, 2019)
AbstractIn Islam, Tawheed is the primary foundation in getting closer to Allah and thus, every Muslim must have good understanding of it.  If the act of worshipping God is not based on right Tawheed, that act will have no value to Allah. According to Sufi masters, the quality of Muslims depends on how well his comprehension of Tawheed is, without which Muslims will never be able to become closer to Allah. Muhammad Nafis al Banjari (born 1150H / 1735) preached his knowledge by teaching the concept of Tawheed in Sufism. This Muslim scholar from South Kalimantan preached by employing bi al-kitÉb, through his work known by al-Durr al-Nafis (1200 H). This qualitative study utilizing the method of library research aimed at finding out and analyzing the thoughts of Muhammad Nafis regarding the concept of Tawheed written in his work. Muhammad Nafis taught Tawheed in Sufism, more specifically to believe and know Allah well by using the eyes of the heart (qalb). By understanding the concept of Tawheed in Sufism, one can reach the level of ma'rifatullÉh, especially to truly know God. Muhammad Nafis’ concept of Tawheed was aimed to straighten people's understanding in Nusantara, more importanly in South Kalimantan, which once was wrong in having thorough understanding of Tawheed. The concept of Tawheed taught in Sufism comprises tauÍid al-afÉ'l, tauÍid al-asma 'tauÍÊd al-SifÉt and tauÍÊd al-DzÉt. The highest knowledge of Tawheed will be achieved if someone has reached ‘fanÉ fÊ Tauhid’, while the highest Tawheed itself is fanÉ fi Allah and baqÉ bi Allah, the sÉlik is called ArÊf bi AllÉh. Muhammad Nafis’ view of the essence of tawheed is similar to the thoughts of prominent Sunni scholars such as al-Junaid, al-Qusyairiy, and al-Ghazali. Within the perspective of right Tawheed, people will achieve the level of ma'rifatullÉh after having arrived at such maqÉmKeywords: tawheed, Muhammad Nafis, al-Durr al-Nafis, fana, baka '. AbstrakDalam Islam ilmu tauhid merupakan landasan utama dalam ber-taqarrub kepada Allah, oleh karena setiap muslim harus memahami ilmu tauhid secara benar. Ibadah tanpa dilandasi tauhid yang benar, tidak ada nilainya dihadapan Allah SWT. Menurut ahli tasawuf kualitas seseorang tergantung pemahaman dalam ber-tauhid, tanpa demikian seseorang tidak akan dapat taqarrub kepada Allah secara hakiki. Muhammad Nafis al Banjari (lahir 1150H/1735) mendakwahkan ilmunya dengan mengajarkan konsep tauhid dalam tasawuf. Seorang ulama Kalimantan Selatan ini berdakwah dengan cara bi al-kitÉb, melalui karyanya al-Durr al-Nafis (1200 H). Kajian yang bersifat kualitatif dengan metode library research ini bertujuan untuk mengetahui dan menganalisa pemikiran Muhammad Nafis mengenai konsep tauhid yang ditulis dalam karyanya itu. Muhammad Nafis mengajarkan ilmu tauhid dalam tasawuf, yaitu meyakini dan mengenal Allah secara hakiki dengan menggunakan matahati (qalb). Dengan memahami konsep tauhid dalam tasawuf, seseorang akan dapat mencapai tingkatan ma’rifatullÉh yaitu mengenal Allah secara hakiki. Dakwah Muhammad Nafis mengenai konsep tauhid itu bertujuan meluruskan pemahaman masyarakat di Nusantara khususnya di Kalimantan Selatan yang salah dalam memahami tauhid secara hakiki. Konsep tauhid dalam tasawuf yang diajarkan itu meliputi, tauÍid al-afÉ’l, tauÍid al-asma’ tauÍÊd al-SifÉt dan tauÍÊd al-DzÉt. Ilmu Tauhid tertinggi akan dicapai apabila seseorang telah mencapai ‘fanÉ fÊ Tauhid’ sedangkan punca tauhid tertinggi adalah fanÉ fi Allah dan baqÉ bi Allah, si sÉlik dinamakan ArÊf bi AllÉh. Pandangan Muhammad Nafis mengenai tauhid yang hakiki ini ada kesamaan dengan pemikiran para ulama-ulama Sunni yang masyhur seperti al-Junaid, al Qusyairiy dan al-Ghazali. Apabila telah sampai kepada maqÉm itu ia mendapatkan ma’rifatullÉh, inilah pandangan tauhid yang hakiki. Kata kunci: Tauhid, Muhammad Nafis, al-Durr al-Nafis, fana, baka’.